y=x+16+x^2
y^2=(x+16+x^2)^2
=(x)^2+(16)^2+(x^2)^2+2*x*16+
2*16*x^2 +2*x^2*x[following identity
(a+b+c)^2=a^+b^2+c^2+2ab+2bc+2ca]
=x^2+256+x^4+32x+32x^2+2x^3
=x^4+2x^3+33x^2+32x+256
2007-09-21 19:43:25
·
answer #1
·
answered by alpha 7
·
0⤊
0⤋
Here is an alternative:
y = x + 16 + x²
y = x(1+x) +16
Remember that (a+b)² = a² + b² + 2ab
y² = (x(1+x))² + 32x(1+x) + 256
y² = x²(1+x)² + 32x + 32x² + 256
y² = x²(x²+2x+1) + 32x + 32x² +256
y² = (x^4) + 2(x^3) + x² + 32x + 32x² + 256
y² = (x^4) + 2(x^3) + 33x² + 32x + 256
2007-09-22 03:34:18
·
answer #2
·
answered by Daniel 4
·
0⤊
0⤋
if y=x+16+x^2
y^2 = (x+16+x^2)(x+16+x^2)
y^2 = x^2 + 16x + x^3 +16x +256 +16x^2 + x^3 + 16x^2 + x^4
y^2 = 32x + 2x^3 +256 + 33x^2 + x^4
2007-09-22 02:38:20
·
answer #3
·
answered by 037 G 6
·
0⤊
0⤋
Just Simple....Multiply this by itself and the answer is
y^2 = 32x + 2x^3 +256 + 33x^2 + x^4
2007-09-22 05:07:58
·
answer #4
·
answered by Adeel 2
·
0⤊
0⤋
y^2 = (x+16+x^2)*(x+16+x^2). You can work out the rest
2007-09-22 02:34:44
·
answer #5
·
answered by zi_xin 5
·
0⤊
2⤋
y=x^2+x+16
y^2=(x^2+x+16)(x^2+x+16)
y^2=x^4+2x^3+33x^2+32x+256
2007-09-22 02:43:16
·
answer #6
·
answered by j_con999 2
·
0⤊
0⤋
y=x+16+x^2?
then y^2=(x^2+(16+x))^2
y^2=x^4+2x^2*(16+x)+(16+x)^2
y^2=x^4+32x^2+2x^3+256+32x+x^2
y^2=x^4+2x^3+33x^2+32x+256
2007-09-22 02:36:04
·
answer #7
·
answered by ptolemy862000 4
·
0⤊
0⤋
Do your own school work.
2007-09-22 02:39:02
·
answer #8
·
answered by night_taker_1999 2
·
1⤊
0⤋
?
2007-09-22 02:38:09
·
answer #9
·
answered by Anonymous
·
0⤊
3⤋